Financialisation as a result of the network economy's development - Joanna Cichorska; Monika Klimontowicz (e-Finanse: Financial Internet Quarterly, 2016)
In the last thirty years, the world's economies have changed significantly. New technology developments have enabled the transition from the industrial economy to the network economy. The network economy is based on information technology, connectivity and human knowledge. Its development has caused changes in the way of life, consumer behaviour on the markets and companies' business models, especially the process of goods and services creation and distribution. Electronic commerce and services have become one of the fastest developing fields of the economy. As a result, the role of government has diminished while the role of markets has increased economic transactions between countries and their citizens have substantially risen, and financial transactions have grown remarkably. This changing landscape has been characterised by globalization and financialisation. The increasing role of financial motives, financial markets, and financial institutions have influenced domestic and international transactions. A new category of finance called e-finance has been created and implemented. Despite the advantages of electronic finance networks, concurrently there are some disadvantages of their diffusion. The purpose of the paper is to present both aspects of financialisation and its influence on the financial and banking system. This purpose determines the structure of the paper. As financialisation is a relatively new term the first section of the paper focuses on defining its phenomenon. This part presents different authors' perspectives and definitions. Next, the influence of financialisation on the Polish financial system's quantitative and qualitative structure is discussed. The last section focuses on the current role and functions of banks in the finance system network structure as a result of a rapidly changing technological environment.
Keywords: G21; D53; O33; O43; 330; financialisation; network economy; banking network structure